ESTABLISHMENT OF A COORDINATION INFORMATION-ANALYTICAL CENTER FOR AUTOSANITATION: MANAGERIAL AND INSTITUTIONAL PERSPECTIVES - Яцюк, Олег (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2025)
The article investigates and conceptualizes the autosanitation ecosystem of an enterprise as an innovative approach to anti-crisis management in an unstable economic environment. It is established that existing scientific works, despite significant achievements in certain areas, do not provide a holistic understanding of the interaction of multiple stakeholders, and a comprehensive toolkit for preventive anti-crisis response is lacking. The relevance of a systemic approach, which allows for the integration of the enterprise's internal capabilities with a wide range of external support, is substantiated. A developed scheme of the integral autosanitation system is presented, representing the enterprise as a central subject, where three key internal groups are identified: owners, management, and employees. The role of each group is analyzed in detail, with particular emphasis on the possibility of involving personnel in financing rehabilitation measures through receiving a part of their salary in securities, which enhances their motivation and investment participation. The system is coordinated by an information and analytical center, which accumulates and transmits support from three external blocks: financing and credit support (commercial banks, suppliers, investors, venture and grant funds); consulting, expert, and scientific support (consulting, legal, auditing companies, scientific institutions, associations, the National Association of Arbitration Managers of Ukraine); and infrastructure and regulation (clearing centers, state bodies, exchanges, and trading platforms). The objective need for and expediency of creating a specialized coordination information and analytical center for autosanitation management and financial provision within the structure of the National Association of Arbitration Managers of Ukraine is substantiated. The main functions of such a center are defined: informational and analytical, coordinating, methodical and educational, and financial engineering. It is noted that the functioning of such a center will contribute to reducing the number of bankruptcy procedures, increasing the trust of creditors and investors, strengthening the role of the National Association of Arbitration Managers of Ukraine in the national anti-crisis governance system, and creating a new architecture for solvency support based on principles of partnership, objectivity, and trust. This will allow for a transition from reactive to preventive mechanisms of crisis management, ensuring sustainable enterprise recovery.